2020
DOI: 10.1002/brb3.1616
|View full text |Cite
|
Sign up to set email alerts
|

Are working memory and glutamate concentrations involved in early‐life stress and severity of psychosis?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 99 publications
(201 reference statements)
0
11
0
1
Order By: Relevance
“…Five studies [93][94][95][96][97] reported findings on the association between the frequency of CT and positive symptom severity (Table 4). An additional study focused on severity of delusions 98 in a large BD sample.…”
Section: Childhood Trauma and Mood And Psychotic Symptomsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies [93][94][95][96][97] reported findings on the association between the frequency of CT and positive symptom severity (Table 4). An additional study focused on severity of delusions 98 in a large BD sample.…”
Section: Childhood Trauma and Mood And Psychotic Symptomsmentioning
confidence: 99%
“…Different CT scores were used across studies, ranging from a total CT score 93,[95][96][97] to scores for subtypes of CT (for example, physical neglect). 93 None of the five studies reported a significant correlation with total CT scores in individuals with first-episode or chronic BD. However, increased severity of delusions was associated with increased total CT scores.…”
Section: Childhood Trauma and Mood And Psychotic Symptomsmentioning
confidence: 99%
See 3 more Smart Citations